Normal stages of embryonic development of a brood parasite, the rosy bitterling Rhodeus ocellatus (Teleostei: Cypriniformes). (2nd April 2021) - Yi, Wenjing; Rücklin, Martin; Poelmann, Robert E.; Aldridge, David C.; Richardson, Michael K.
Abstract: Bitterlings, a group of freshwater teleosts, provide a fascinating example among vertebrates of the evolution of brood parasitism. Their eggs are laid inside the gill chamber of their freshwater mussel hosts where they develop as brood parasites. Studies of the embryonic development of bitterlings are crucial in deciphering the evolution of their distinct early life‐history. Here, we have studied 255 embryos and larvae of the rosy bitterling ( Rhodeus ocellatus ) using in vitro fertilization and X‐ray microtomography (microCT). We describe 11 pre‐hatching and 13 post‐hatching developmental stages spanning the first 14 days of development, from fertilization to the free‐swimming stage. In contrast to previous developmental studies of various bitterling species, the staging system we describe is character‐based and therefore more compatible with the widely‐used stages described for zebrafish. Our bitterling data provide new insights into to the polarity of the chorion, and into notochord vacuolization and yolk sac extension in relation to body straightening. This study represents the first application of microCT scanning to bitterling development and provides one of the most detailed systematic descriptions of development in any teleost. Our staging series will be an important tool for heterochrony analysis and other comparative studies of teleost development, and may provide insight into the co‐evolution of brood parasitism. Abstract : A selection of microCT images of rosy bitterling embryos.